Autonomy : The Social Ontology of Art under Capitalism - Brown, Nicholas, 1971- (Book collections on Project MUSE., 2019)
Nicholas Brown theorizes the historical and theoretical conditions for the persistence of art's autonomy from the realm of the commodity by showing how an artist's commitment to form and by demanding interpretive attention elude the logic of capital.